Antifungal susceptibility and characterization of Alternaria alternata causing leaf spot disease on Aloe vera (L.) Burm. f. in India (IASH Indian Journal of Arid Horticulture, 2026)
Leaf spot is destructive disease of Aloe vera and the disease incidence during 2021-22 was varying 50-100%. The symptoms initially appeared as minute circular, water-soaked lesions on the adaxial surface of leaves, which later developed into depressed dark brown to black necrotic spots. The associated pathogen was isolated in pure culture on PDA exhibited rapid growth, initially light grey to olive green, which gradually turned dark brown to black with abundant sporulation. The colony surface typically showed concentric zonation, while the reverse side of the plate appears dark brown to black pigmentation. Further, ITS region was sequenced, and based on morphological and molecular sequences the pathogen was identified as Alternaria alternata. The pathogen found highly sensitive to the fungicides Difenoconazole under In-vitro conditions, and was found to be the most effective in inhibiting mycelial growth of the test pathogen Alternaria alternata.